Towards a product independent ERP training model: An Insight from a literature review - Seyed Mohammad Motahar (Australasian Journal of Information Systems, 2018)
ERP can be called as one of the most significant contributions of computer science and particularly information systems for the business environment which can support all complicated business process of an organisation including sale, purchase, warehouse and manufacturing into a single database. For such complex system like ERP, implementation involves much collaboration which raises the concern of the success of the project. Among most significant success and failure factors of ERP implementation cited in the literature are training and consultation. For many years the majority of ERP vendors promote their product specific training models as long-term and expensive allowing the organisation to gain knowledge of the ERP system and the way it handles the business process. However, recent studies showed that ERP training can be conducted in the short term and with minimum investment and yet to be effective. Findings triggered a signal and opened a new door for research to investigate vendor-independent training models that require limited investment in training and consultancy. This paper aims to provide an overview of the literature; highlighting the research methods and theories used by authors towards building ERP training models and methods.